Evoking the Teachings of Iranian Political wisdom in Farabi's Political Thought - Tayebeh Mohammadi kia (رهیافتهای سیاسی و بین المللی)
Farabi is considered the founder of philosophy in the Islamic world. This Iranian philosopher not only entered of Greek reason into the field of Muslim knowledge, but also entered the Iranian politics to the Islamic political system. In fact, Farabi's political thought has various sources. We should consider him as the inheritor of the presence of Platonic philosophy, Aristotelian reason, Iranian wisdom, Islamic knowledge, and Shiite teachings of his time. The aim of this study is recognizing and analyzing the presence and extension of Iranian wisdom in Farabi's political thought. Farabi describes thinking in the field of Iranian wisdom in ontology, epistemology, society and politics. His ontology is linked to Iranian wisdom by following the example of the series of angels and the connection of heaven and earth, and in the field of social life, it is an ideal format for his utopia. Furthermore, Farabi's epistemology, which ultimately leads to the supremacy of fantasy, has its roots in Iranian light based Imagination; The wisdom bridges the light of knowledge and awareness between the earth and the sky. In his thought, politics should establish a connection between the sky and the seal of God with the royal throne and the people of the society. These three components have Iranian origins. He considered Farabi's political thought in the style of royal governance and undeniable examples of Iranian wisdom.